GE_GERICHTE P/5662/2018 vom 17. Juni 2019 - GE Cour de justice (2019)
PLAINTE PÉNALE;DÉLAI;ACCÈS INDU À UN SYSTÈME INFORMATIQUE;SOUSTRACTION DE DONNÉES(ART. 143 CP);CONCURRENCE DÉLOYALE | CP.31; CP.143; CP.143bis; CPP.310; LCD.23